Lepidium cake as a feed stuff to pigs - Arefaine, Hagos (2016)
The purpose of this study was to evaluate the effect of different levels of lepidium cake (LC) on palatability, coefficient of total tract digestibility (CTTAD), blood parameters and feeding behaviour in growing pigs. A total of 8 female growing pigs ((Land race x Yorkshire) × Hampshire) with an average initial body weight of 26.5±2.5 kg were used in the trail which lasted for 44 days. The pigs were fed four experimental diets (control, LC4: 4% of Lepidium cake + 96 % control; LC8: 8% of Lepidium cake + 92 % control; LC12: 12% of Lepidium cake + 88% control) in a double 4 × 4 Latin square design. The contol diet was composed of barley, wheat, soya bean protein, amino acids, premix and Ti0₂. Feed intake, faecal and blood samples, as well as feeding behavioral datas were collected and analysed. The result of current study showed that the total non-starch polysahharides (NSP) and dietary fiber (DF) content increased with increasing LC. The CTTAD of dry matter (DM), organic matter (OM), crude protein (CP) and gross energy (GE), decreased (P <0.01) with inclusion of LC.This was mainly due to high proportion of indigestable fiber in the LC. The CTTAD of EE was increasing with inreasing inclusion levels of LC. Except for EE, the CTTAD of the basal diet was higher (P<0.01) than the diets with different inclusion levels of LC. Blood parameters, feed choice, and feeding time were not affected by inclusion levels of LC (P>0.05). However, feeding rate, rooting, searching, throwing and moving feed showed a tendency to be significant (P = 0.01). LC is palatable to growing pig, but lower digestibility due to high proportion of indigestible fiber in the diet. The regression model was poor to explain the source of variation. The lack of significant difference among test diets for blood, CTTAD and feeding behavior could be due to low levels of inclusion level of LC. The digestibility of LC at 100 % inclusion level is low (< 40%), this implies that the LC is poorly digestible by growing pig. Hence, strategies like dehulling of husk, supplementation of exogenous enzyme; alkali treatment such as sodium hydroxide (NaOH) could improve the CTTAD of LC. Furthermore, developing lepidium varieties having less fiber and glucosinolate content might sustainably improve the utilization of LC by growing pigs.